Measuring the Impact of Air Pollutants on Ecological Footprint, Forest Area and Cropland - Irfan, Muhammad; Cherian, Jacob; Abdul Rahman, Abdul Aziz; Haddad, Akram M.; Sial, Muhammad Safdar; Ali, Basit; Brugni, Talles Vianna (International Journal of Energy Economics and Policy, 2022)
The purpose of this study is to investigate the impact of air pollutants including carbon dioxide emissions (CO2), Nitrogen oxides (NOx) and nitrous oxide (NO2) over the period 1975 to 2020 on ecological footprint, Forest area and cropland. The study used GDP and trade openness as control variable in establishing the long run and short relationship between air pollutants and ecological footprint and its sub-components. The study used Johannsson co-integration and error correction model co-integrating relationship and elasticities. The study found that there exist at least three cointegrating equations for ecological footprint and forest area while four cointegrating equation for cropland. The results shows that model CO2, NO2 and TOP reduces the pressure on EF in long run while NOx and GDP damage the EF by utilizing more natural resources during production of goods and services. However, CO2 concentration increases as forest area increases while NOx damage the cropland. The ECM shows that speed of adjustment is 90% for forest area and 50% and 40% for EF and cropland respectively. Carbon overdose is mainly caused by fossil fuel burning and forest destruction, which continuously accumulates as a result of industrialization. The study found that pollutants, such as CO2, NO2 and NOx also potential to damage ecosystems and only clean air is a desirable policy option for green economy.